68 - INFORMATION ON RISKS AND WORK SATISFACTION AMONG WORKERS OF NURSING A UNIVERSITY HOSPITAL IN NATAL, RN, BRAZIL (Fiep Bulletin - online, 2011)
Introduction: The nursing staff is very vulnerable to exposure to biological material. This large number of exhibits related to the fact that health workers have direct contact in patient care and also the type and frequency of procedures performed. Objectives: This study sought to identify the information of nursing that can encourage them to accidents at work and verify compliance with the professional work, facing the risks of accidents in the workplace. Methodology: This study was descriptive epidemiological performed through a retrospective survey of 100 nursing workers at the Onofre Lopes University Hospital (HUOL), located in Natal / RN, Brazil. Data were collected from September to December 2006 using a questionnaire consisting of both open and closed. Results: the analyses revealed that information regarding factors that can cause accidents at work were stress and handling with cutting and piercing material among nursing assistants. Nursing technicians cited repetitive work, stress, sleep and fatigue. The nurses believe the hospital infection, material cutting and piercing stress. The job satisfaction, 46% of workers have shown dissatisfaction, 43% are satisfied and 11% are very satisfied. In general, it is observed that the dissatisfaction is generated by the working conditions and satisfaction is perceived by the love and dedication to work and chosen profession. Conclusion: We conclude that changes are needed in the workplace to minimize risks in the handling procedures and work environment, as well as training, awareness of security and provision of safety devices for workers.
Keywords: nursing worker; worker satisfaction; work accident hospital